Statistical literacy in primary education: An analysis of Indonesian fifth-graders' data interpretation and analysis skills - Hasanah, Uswatun; Putrawangsa, Susilahudin; Setiawati, Farida Agus; Purwanta, Edi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Statistical literacy is an essential competency in today’s data-driven society. However, research in this field often overlooks primary-level students, focusing predominantly on those in higher education. To address this gap, the present study evaluated the statistical literacy of 50 fifth-grade students in Indonesia, with a focus on their abilities in data analysis and interpretation. Utilizing a descriptive cross-sectional design, the study employed a written test grounded in real-world data scenarios, adapted from established theoretical frameworks. The assessment included various data representations—pictograms, bar charts, tables, and line charts—designed to evaluate students’ skills in comprehension, comparison, and interpretation. The results indicate that the majority of students operated at an Idiosyncratic level, demonstrating limited capacity for data interpretation, while a smaller proportion reached the Transitional level; notably, no students attained Quantitative or Analytical proficiency. These findings underscore the urgent need for curriculum reforms to enhance both computational and analytical skills at an early stage, thereby equipping students with the foundational competencies required for advanced data reasoning. Future research should investigate pedagogical strategies that can bridge early-stage statistical literacy with the demands of higher-level statistical reasoning, ensuring students are better prepared for a data-intensive world.